Characterization of silane treated Malaysian Yankee Pineapple AC6 leaf fiber (PALF) towards industrial applications - Najeeb, M.I.; Sultan, M.T.H.; Andou, Yoshito; Shah, A.U.M; Eksiler, Kubra; Jawaid, M.; Ariffin, A.H. (Elsevier, 2020)
This research studied the effects of silane treatment at different soaking time: 1, 3, 5 h,on the properties of new variant Yankee’s Pineapple AC6 leaf fiber (PALF). The propertiesof untreated and treated PALF was evaluated through several testing. The Si element wasfound on all treated fiber’s surface through Energy-Dispersive X-ray, while significant peakswere clearly seen for these treated fibers at 1317.81 and 1100 cm−1by Fourier TransformInfrared Spectroscopy. X-Ray Diffractor analyses showed small changes on the crystallinityof all treated fiber disregards the treatment and soaking time as compared to untreatedfiber. Improvement on the degradation temperature of all treated fibers to 360◦C from 340◦C was seen from the thermogravimetric analysis. Maximum surface roughness and tensilestrength were found for treated fibers at 3 h soaking time by atomic force microscope andsingle fiber testing respectively. The analyses suggested the potential Yankee’s PALF to beused in composites for various industrial applications.